Determining the Effects of Operating Conditions on Current Density of a PEMFC by Using Taguchi Method and ANOVA - Bayrak, Zehra Ural; Celik, Nevin (Springer Heidelberg, 2024)
Proton Exchange Membrane Fuel Cells (PEMFCs) used in Unmanned Aerial Vehicles (UAVs) have an important place in the aviation industry and mostly operate under high current density conditions. Notably the operating temperature, the fuel supply pressure and volumetric flow rates of air and fuel can be counted among the important parameters that affect the high current density. Therefore, a comprehensive optimization analysis becomes inevitable. In present study, it is aimed to optimize the operating conditions that are considered to be effective on the current density of a PEMFC, by applying the well-known Taguchi Design of Experiment (DoE) method. Current density values of a selected PEMFC have been calculated by MATLAB/Simulink commercial software. The number of simulations is determined by Taguchi method. The most suitable orthogonal array L18, is utilized to identify the optimal factor conditions. The contribution ratio of each parameter on the current density is revealed by Analysis of Variance (ANOVA). The confirmation is supplied by confirmation tests. The optimum values for the current density are obtained when the operating temperature is 313 K, the fuel flow rate is 50 lpm, the air flow rate is 300 lpm and the fuel supply pressure is 1.5 bar. The contribution ratios of cell temperature, supply pressure, flowrate of fuel and flowrate of air are, respectively, found to 69.7%, 16.6%, 6.7% and 0.9%.
Keywords: Taguchi method; ANOVA; PEMFC; Optimization